2023
DOI: 10.37934/araset.30.3.222235
|View full text |Cite
|
Sign up to set email alerts
|

Human Detection from Drone using You Only Look Once (YOLOv5) for Search and Rescue Operation

Abstract: Drones are unmanned aerial vehicles that can be remotely operated to perform a variety of tasks. They have been used in search and rescue operations since the early 2000s and have proven to be invaluable tools for quickly locating missing persons in difficult terrain and environment. In certain cases, automated human detection on drone camera feed can help the responder to locate the victims more effectively. In this work, we propose the use of a deep learning method called You Only Look Once version 5, or YOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, the demand of technologies and approach for research is now relatively high as the technologies tend to develop rapidly. As an example, Kaamin et al, [6], demonstrated the utilization of UAVs for roof inspection, and the research conducted by Zaman et al, [7], employed UAVs and YOLOv5 for human detection in search and rescue operations, exemplify the increasing adoption of innovative solutions and technologies in various fields, highlighting the continuous development and integration of UAVs for diverse applications. Another study by Mokhtar et al, [8] and Siddiq et al, [9] demonstrate the ongoing research efforts in utilizing UAV photogrammetry to assess and understand coastal erosion phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the demand of technologies and approach for research is now relatively high as the technologies tend to develop rapidly. As an example, Kaamin et al, [6], demonstrated the utilization of UAVs for roof inspection, and the research conducted by Zaman et al, [7], employed UAVs and YOLOv5 for human detection in search and rescue operations, exemplify the increasing adoption of innovative solutions and technologies in various fields, highlighting the continuous development and integration of UAVs for diverse applications. Another study by Mokhtar et al, [8] and Siddiq et al, [9] demonstrate the ongoing research efforts in utilizing UAV photogrammetry to assess and understand coastal erosion phenomena.…”
Section: Introductionmentioning
confidence: 99%